Pengaruh Adopsi Sistem Pembayaran Hybrid Terhadap Efektivitas Pengelolaan Keuangan UMKM di Kota Palu: Peran Moderasi Literasi Keuangan - Apriliani, Sindi; Yunus Kasim, Muhammad; Darman; Samudra, Suryadi (JURNAL MANAJEMEN MOTIVASI, 2026)
The increasing use of hybrid payment systems among MSMEs requires evidence of their impact on financial management effectiveness. This study examines the effect of hybrid payment system adoption on the financial management effectiveness of MSMEs in Palu City, with financial literacy as a moderating variable. A quantitative approach was employed using data from 60 MSMEs selected through purposive sampling and analyzed with Moderated Regression Analysis (MRA). The findings indicate that hybrid payment system adoption positively and significantly improves financial management effectiveness, while financial literacy weakens this relationship. These findings highlight the importance of integrating digital payment adoption with financial literacy development to enhance MSME financial management.